1999
DOI: 10.1161/01.str.30.10.2131
|View full text |Cite
|
Sign up to set email alerts
|

The Stroke Impact Scale Version 2.0

Abstract: Background and Purpose-To be useful for clinical research, an outcome measure must be feasible to administer and have sound psychometric attributes, including reliability, validity, and sensitivity to change. This study characterizes the psychometric properties of the Stroke Impact Scale (SIS) Version 2.0. Methods-Version 2.0 of the SIS is a self-report measure that includes 64 items and assesses 8 domains (strength, hand function, ADL/IADL, mobility, communication, emotion, memory and thinking, and participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
369
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 976 publications
(375 citation statements)
references
References 24 publications
4
369
1
1
Order By: Relevance
“…The SIS has been suggested as the optimal PROM for this purpose as it has been shown to be reliable, valid, and sensitive to change 14. However, there are examples of clinical studies where SIS was used as an end‐point measure and, as a result of perceived burden, questionnaire return rates were so poor as to invalidate the study 15.…”
Section: Discussionmentioning
confidence: 99%
“…The SIS has been suggested as the optimal PROM for this purpose as it has been shown to be reliable, valid, and sensitive to change 14. However, there are examples of clinical studies where SIS was used as an end‐point measure and, as a result of perceived burden, questionnaire return rates were so poor as to invalidate the study 15.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes used to measure UE motor function were the Wolf Motor Function Test (Morris, Uswatte, Crago, Cook, & Taub, 2001), including the Functional Ability and Performance Time scales; the Fugl-Meyer Assessment (FMA; Gladstone, Danells, & Black, 2002); and the Nine-Hole Peg Test (Chen, Chen, Hsueh, Huang, & Hsieh, 2009). Nonmotor function was assessed using the Center for Epidemiologic Studies Depression Scale (Shinar et al, 1986), the Stroke Impact Scale (SIS; Duncan et al, 1999), and the Trail Making Test Parts A and B (Tamez et al, 2011). Outcomes for cardiopulmonary function were a CPX test and the Six-Minute Walk Test (6MWT; Fulk, Echternach, Nof, & O'Sullivan, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…It also addresses overall percentage of recovery from the stroke, which is categorized as a domain in this article. The SIS has been shown to be valid and reliable in people with stroke (Duncan et al, 1999).…”
Section: Outcome Measures and Randomizationmentioning
confidence: 99%
“…An emerging body of evidence has shown promising results with improved motor recovery and improvement on QOL measures with the use of robotic devices after stroke (Bovolenta, Sale, Dall'Armi, Clerici, & Franceschini, 2011;Page, Hill, & White, 2013;Posteraro et al, 2009). Page et al (2013) found that after 24 sessions with an upperextremity (UE) robot-assisted therapy device, people with chronic stroke made favorable gains in the ADL and Instrumental Activities of Daily Living (IADL), Hand Function, and Stroke Recovery domains of the Stroke Impact Scale (SIS; Duncan et al, 1999), a QOL measure used after stroke (Page et al, 2013). We previously reported significant improvements in several domains of the SIS after 30 hr of an in-clinic robot-assisted therapy intervention combined with 30 hr of repetitive task practice (Kutner et al, 2010).…”
mentioning
confidence: 99%